Modalização e polifonia no gênero resenha acadêmica:um olhar apreciativo sobre a voz da ciência - Barbosa, Maria vanice Lacerda de Melo (2015)
In order to building a spoken or written text, regardless of gender that it is being carried out, the speaker uses linguistic features such as semantic-argumentative strategies intending to guide the interlocutor to certain conclusions. The modalization and polyphony, accordingly, are phenomena that allow the speaker to leave printed his subjectivity in the content of the statements, while acting according to his interlocutor. Focusing in these discussions, this investigation aims to show that modalization and polyphony reveal, linguistically, subjectivity in the digest genre, acting therefore as argumentation features. It is a qualitative research, descriptive and interpretative, which adopts the theoretical and methodological principles of Argumentative Semantics. The corpus consists of ten digests collected in six editions of the Jornal de Resenhas, of the Discurso Editorial, ISSN 1984-6282, published in 2009, 2010 and 2012. The theoretical discussions concerning the Argumentation Theory of Language have based in Ducrot (1994, 1987, 1988), Espíndola (2004), Nascimento (2005, 2009), Koch (2006a, 2006b) and others arguing about the theory approach. The modalization is discussed under the postulates of Castilho and Castilho (1993), Koch (2006b), Cervoni (1989), Nascimento (2009), Neves (2011a), Palmer (2011) and García Negroni (2011). Besides, it was used as theoretical basis, Foucault (2011), Bakhtin (2010a, 2010b), Marcuschi (2008) and others to the formulations about the digest genre. The analysis reveals that digesters use modalization and the polyphony of speakers as phenomena that ultimately report the speakers‟ subjectivity in relation to the view of the voices of other speakers, that is, as a discursive strategy that guides the way the text of the digest should be read. Thus, the gender digest is defined as a place of interaction of voices and subjective impressions through which the speaker summarizes praises, criticizes and evaluates the most diverse academic intellectual productions.